Immunomodulating effects of the anti-viral agent Silibinin in liver transplant patients with HCV recurrence. Issue 1 (December 2016) - Castellaneta, Antonino; Massaro, Antonio; Rendina, Maria; D'Errico, Francesca; Carparelli, Sonia; Rizzi, Salvatore Fabio; Thomson, Angus; Di Leo, Alfredo
Abstract Background Silibinin has been shown to have anti-HCV activity and immune-modulating properties by regulating dendritic cell (DC) function. DCs are antigen-presenting cells that, together with regulatory T cells (Treg), play a pivotal role in controlling alloimmune, as well as anti-HCV immune responses. Methods Twelve liver transplant patients with HCV recurrence received iv infusion of Silibinin (iv-SIL) for 14 consecutive days. Using flow cytometry, before and at the end of treatment, we determined the frequencies of circulating myeloid (m) and plasmacytoid (p) DC and Treg and the expression of costimulatory/coregulatory molecules by the DC subsets and Treg. Statistical analysis was performed using the paired Student'st test and Pearson correlation test. Results After iv-SIL treatment, we observed an elevated plasmacytoid dendritic cell (pDC)/myeloid dendritic cell (mDC) ratio, while pDC displayed lower HLA-DR and higher immunoglobulin-like transcript 4 (ILT4), CD39, and HLA-G expression compared to the pretreatment baseline. In addition, after iv-SIL, mDC showed increased inducible costimulator ligand (ICOSL) expression. No changes were detected in Treg frequency or programed death (PD)-1 expression by these cells. Moreover, several correlations between DC/Treg markers and clinical parameters were detected. Conclusions This descriptive study, in liver transplant patients with HCV recurrence, reveals the impact of iv-SIL on DC and Treg. The changes observed in circulating pDC and mDC that have previously been associated with tolerogenic conditions shed new light on how iv-SIL may regulate anti-viral and alloimmunity. We have also observed multiple clinical correlations that could improve the clinical management of liver transplant patients and that deserve further analysis.